2020
DOI: 10.1016/j.jand.2020.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Lunch on School Days in Canada: Examining Contributions to Nutrient and Food Group Intake and Differences across Eating Locations

Abstract: Background Recent federal proposals in Canada have called for changes in the delivery and funding of school lunches. Yet little evidence has documented the nutritional quality of meals eaten by school children, which is needed to inform school lunch reforms. Objectives To assess the dietary contributions of lunch foods to daily food and nutrient intakes on school days and compare dietary intakes across eating locations (school, home, and off campus). Design Cross-sectional analyses of school day data from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 45 publications
2
11
0
Order By: Relevance
“…We are working with a community-based organization that works with local producers to incorporate local foods where possible into school food menus. The menu includes a variety of vegetables and fruits because they are particularly low in the diets of Canadian children [ 14 , 46 ], and it has been reviewed by a dietitian.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We are working with a community-based organization that works with local producers to incorporate local foods where possible into school food menus. The menu includes a variety of vegetables and fruits because they are particularly low in the diets of Canadian children [ 14 , 46 ], and it has been reviewed by a dietitian.…”
Section: Methodsmentioning
confidence: 99%
“…Provision of healthy school lunches is challenging in the context of parents working long hours [ 43 , 44 ], and families are struggling to adopt healthy food behaviors [ 44 ]. Parents may rely on highly processed foods, low in key nutrients but high in salt, sugar, and fat, to cope with demands on time [ 45 , 46 ]. The diets of Canadian children across the socioeconomic spectrum are poor [ 47 ].…”
Section: Introductionmentioning
confidence: 99%
“…Students consumed lower than recommended amounts of dark green and orange vegetables, whole fruit, whole grains, milk and alternatives, vitamin D and calcium, and higher amounts of sodium (Tugault-Lafleur & Black, 2020).…”
Section: Literature Reviewmentioning
confidence: 93%
“…A more recent analysis of British children aged 1.5-18 years concluded that the home and school eating environments are associated with better food choices, while other locations including outlets selling foods to eat on the go are associated with poorer food choices [18]. These results mimic the rest of Europe and Canada, where the home and school environments are associated with a higher consumption of desirable nutrients and a diet lower in energy density in adolescents [24,25].…”
Section: Introductionmentioning
confidence: 98%